2013
DOI: 10.3109/14659891.2012.707285
|View full text |Cite
|
Sign up to set email alerts
|

Chronic promethazine misuse and the possibility of dependence: a brief review of antihistamine abuse and dependence

Abstract: Promethazine, a phenothiazine derivative antihistamine, has not been considered to be associated with problems with dependency. A unique case, with features fulfilling the criteria of drug dependence following several years of misuse of high dose promethazine is presented. Literature relating to the abuse of promethazine and other

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…Consistent with previous observations ( Agnich et al, 2013 ; Burns and Boyer, 2013 ; Carr, 2006 ; Elwood, 2001 ; Höjer and Tellerup, 2018 ; NIDA, 2014 ; Page et al, 2009 ; Parker et al, 2013 ; Peters et al, 2007 ), most recorded ADRs related here to either ‘drug abuse’ and ‘intentional product misuse’, involving young adult (19–25 years) males. Although considered a vulnerable category with respect to prescription drug abuse ( Agnich et al, 2013 ; Burns and Boyer, 2013 ; Cherian et al, 2018 ; NIDA, 2014 ; Peters et al, 2007 ), adolescents (10–18 years) were here reported in only a minority (23/1543:1.5%) of cases.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with previous observations ( Agnich et al, 2013 ; Burns and Boyer, 2013 ; Carr, 2006 ; Elwood, 2001 ; Höjer and Tellerup, 2018 ; NIDA, 2014 ; Page et al, 2009 ; Parker et al, 2013 ; Peters et al, 2007 ), most recorded ADRs related here to either ‘drug abuse’ and ‘intentional product misuse’, involving young adult (19–25 years) males. Although considered a vulnerable category with respect to prescription drug abuse ( Agnich et al, 2013 ; Burns and Boyer, 2013 ; Cherian et al, 2018 ; NIDA, 2014 ; Peters et al, 2007 ), adolescents (10–18 years) were here reported in only a minority (23/1543:1.5%) of cases.…”
Section: Discussionsupporting
confidence: 89%
“…data on worldwide promethazine prescriptions) are not available, it was unclear if what observed was a substantial number of cases, indicative of clinically meaningful abuse potential, or a passing trend for promethazine misuse by a very small number of individuals. However, consistent with previous suggestions (Montastruc et al, 2011), the value of the current study was that its rationale was driven by a proper, detailed, Tellerup, 2018;NIDA, 2014;Page et al, 2009;Parker et al, 2013;Peters et al, 2007), most recorded ADRs related here to either 'drug abuse' and 'intentional product misuse', involving young adult (19-25 years) males. Although considered a vulnerable category with respect to prescription drug abuse (Agnich et al, 2013;Burns and Boyer, 2013;Cherian et al, 2018;NIDA, 2014;Peters et al, 2007), adolescents (10-18 years) were here reported in only a minority (23/1543:1.5%) of cases.…”
Section: Limitationssupporting
confidence: 76%
See 1 more Smart Citation
“…The concoction is probably named after the color of the syrup’s dye and pursued in order to achieve euphoric and relaxing sensations [ 6 , 61 ]. Arrhythmia (manifesting as a prolongation of the QT interval in electrocardiogram), delirium, psychoses, substance dependence, and withdrawal syndrome are some of the known consequences of its misuse, as well as tardive dyskinesia resulting from the antagonism of D 2 dopaminergic receptors [ 62 ].…”
Section: Resultsmentioning
confidence: 99%